A Bibliometric Analysis of 25 Years and 1273 Dissertations in Thoracic and Cardiovascular Surgery - Sarbay, İsmail (Cerrahpaşa Medical Journal, 2024)
Objective: Dissertations play a crucial role in developing research skills and clinical practices and they are required to complete the training program. The transformation of these dissertations into scientific publications is essential for clinicians pursuing academic careers. This study aims to evaluate the dissertations in the field of Thoracic and Cardiovascular Surgery in terms of publication rates and bibliometric parameters, and to analyze these data by making comparisons within and between these fields in Türkiye. Methods: The study included 1273 dissertations in thoracic and cardiovascular surgery registered in the National Thesis Center between 1995 and 2020. Data were obtained from search engines, and bibliometric parameters were collected, including publication status, publication time, research method, author’s gender, affiliation, citation count, and journal index. Statistical analysis was performed using SPSS, and bibliometric networks were visualized using VOSviewer. Results: The overall publication rate was 39.5%, with thoracic surgery at 37.4% and cardiovascular surgery at 40.4%. Dissertations from universities had higher experimental and prospective study rates (17.2%) compared to training and research hospitals (2.9%), showing a significant difference (P < .001). Male researchers had a higher conversion rate of dissertations into articles (40.9%) compared to female researchers (31.7%) (P = .019). Articles published in SCIE journals had a shorter time to publication (3.7 years) and received more citations compared to other indexes (P < .001). Conclusions: The findings indicate that dissertations in thoracic and cardiovascular surgery in Türkiye have comparable publication rates to other medical specialties, with a significant preference for SCIE journals. The study highlights the need for improved research infrastructure in training hospitals. The higher publication rates and shorter publication periods of experimental studies underscore their scientific value and the motivation of researchers in these fields. Cite this article as: Sarbay İ. A bibliometric analysis of 25 years and 1273 dissertations in thoracic and cardiovascular surgery. Cerrahpaşa Med J. 2024;48(3):243-247.